PELAKSANAAN INOVASI PELAYANAN PUBLIK “SAD TO HAPPY” DI KABUPATEN DHARMASRAYA - Azhari Muhammad Hadi Putra; Aidinil Zetra; Roni Ekha Putera (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2023)
The tribal people (SAD) have been living marginally, marginalized because their lifestyle is still nomadic in the jungles of Central Sumatra, making it difficult for them to be able to meet the standard of living as other Indonesian citizens. The Dhamasraya Regency Government is one of the regencies that are the distribution areas of SAD, for this reason the Dhamasraya Regency Government has created public service innovations in the field of population administration, namely the Child Tribe in Forest Breaks for the sake of Population Administration in the dhamasraYa district, abbreviated as (SAD TO HAPPY), as a real effort to carry out its functions regional autonomy with the principle of effective and efficient public service as a whole. This innovation aims to enable the district government to provide direct services to the SAD community in a pro-active way where elements of the local government in collaboration with local community leaders and also non-governmental organizations (NGOs) with activists concerned with SAD, come directly to the location where the existing SAD community lives. in the Dhamasraya district, although they have to break through the jungle to get to that location, so that the SAD community with their limitations no longer has to bother coming to the district center to get population administration services. Writing this journal intends to discuss more deeply how this innovation is carried out, who is involved, how the implementation mechanism is as previously described. The research method used by the author is a literature study with in-depth analysis of news sources and existing scientific theories, writing conclusions This is that the SAD TO HAPPY innovation has succeeded in reaching the SAD community who have been living on the margins and then managed to record their population documentation so that they can use it to get public services. Keywords; Indigenous Child Society (SAD), Innovation, Public Services, Regional Autonomy, Dhamasraya District Government